Expression of Calgranulin Genes S100A8, S100A9 and S100A12 Is Modulated by n-3 PUFA during Inflammation in Adipose Tissue and Mononuclear Cells. - Rachana D Shah; Chenyi Xue; Hanrui Zhang; Sony Tuteja; Mingyao Li; Muredach P Reilly; Jane F Ferguson (PLoS ONE)
Calgranulin genes (S100A8, S100A9 and S100A12) play key immune response roles in inflammatory disorders, including cardiovascular disease. Long-chain omega-3 polyunsaturated fatty acids (LC n-3 PUFA) may have systemic and adipose tissue-specific anti-inflammatory and cardio-protective action. Interactions between calgranulins and the unsaturated fatty acid arachidonic acid (AA) have been reported, yet little is known about the relationship between calgranulins and the LC n-3 PUFA eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). We explored tissue-specific action of calgranulins in the setting of evoked endotoxemia and n-3 PUFA supplementation. Expression of calgranulins in adipose tissue in vivo was assessed by RNA sequencing (RNASeq) before and after n-3 PUFA supplementation and evoked endotoxemia in the fenofibrate and omega-3 fatty acid modulation of endotoxemia (FFAME) Study. Subjects received n-3 PUFA (n = 8; 3600mg/day EPA/DHA) or matched placebo (n = 6) for 6-8 weeks, before completing an endotoxin challenge (LPS 0.6 ng/kg). Calgranulin genes were up-regulated post-LPS, with greater increase in n-3 PUFA (S100A8 15-fold, p = 0.003; S100A9 7-fold, p = 0.003; S100A12 28-fold, p = 0.01) compared to placebo (S100A8 2-fold, p = 0.01; S100A9 1.4-fold, p = 0.4; S100A12 5-fold, p = 0.06). In an independent evoked endotoxemia study, calgranulin gene expression correlated with the systemic inflammatory response. Through in vivo and in vitro interrogation we highlight differential responses in adipocytes and mononuclear cells during inflammation, with n-3 PUFA leading to increased calgranulin expression in adipose, but decreased expression in circulating cells. In conclusion, we present a novel relationship between n-3 PUFA anti-inflammatory action in vivo and cell-specific modulation of calgranulin expression during innate immune activation.